Accounting Standards for the Financial Industry: Addressing Challenges in Measuring Financial Instruments - Duryana Duryana; I Kadek Wira Dharma Prayana; Yulianti Yulianti (Pt. Anagata Sembagi Education, 2024)
This study aims to identify, evaluate, and synthesize literature on accounting standards for the financial industry and the challenges faced in measuring financial instruments. The method used is the Systematic Literature Review (SLR), which includes the steps of literature identification, literature selection, data extraction, and data analysis. The literature analyzed was obtained from various data sources such as Google Scholar, JSTOR, and ScienceDirect using relevant keywords. Literature selection was carried out in three stages: initial selection based on title and abstract, further selection based on full text, and quality assessment using critical appraisal tools such as CASP. The extracted data includes information about the author, year of publication, research objectives, methodology, main results, and recommendations. The results of the study indicate that although international accounting standards have provided a clear framework, challenges in implementation remain, especially related to fair value measurement and market uncertainty. The financial industry needs to adapt to market changes and existing regulations and ensure a system that can manage the complexity of data and calculations in measuring financial instruments. Technology can play an important role, but companies must also be aware of the risk of system errors and fraud in reporting. Periodic evaluation of the measurement methods used can improve the accuracy and transparency of financial reports, which are essential to maintaining stakeholder trust. This research provides useful insights for the development of better accounting standards, as well as for financial companies in facing the challenges of measuring increasingly complex financial instruments.